The Nature of the Pedagogical Skills of Future Music Teachers in Intercultural Education - Marcheva, Penka (Acta Paedagogica Vilnensia, 2016)
The pedagogical skills of a music teacher are discussed in the first part of this article. Presented are the skills that are required of the teacher in terms of an intercultural musical process. A starting position in this process is the children’s communication as much as with their native folklore heritage, as with the musical traditions of other ethnical groups and nations as well. In the second part of this article, listed are pieces of music taught in primary school that are connected with their traditions. This publication is related to a study conducted on a university project, titled “The Approbation of a Technological Interdisciplinary Model of Assessing the Teaching Skills of Students in Terms of Theoretical and Practical Trainings”. Some points of view of the current topic are considered in the theoretical part. As a result of the theoretical research on the problem, the nature of the pedagogical skills in the intercultural musical education of the students from primary school pedagogic has been determined. The methods used in this research are the following: a theoretical analysis of the literature on the studied problem, quantitative and qualitative analyses of the results obtained from research, relative to the musical practical preparation of students from primary school pedagogic.
Keywords: student’s pedagogical skills; future teachers in primary school; intercultural music education